Climate change, food security, and the role of technology in community resilience - Elhassan, Azza; Zeidan, Juliette; Ismail, Abdelbagi; Baru, Joshua; Ogolla, Michelle; Al-Saud, Princess Noura; Al-Shalan, Princess Mashael; Costa, Sergio; Melo, Carla (International Rice Research Institute, 2025)
The climate crisis is no longer a distant threat but a present reality, manifesting as increased droughts, unprecedented floods, and the degradation of critical ecosystems. While the global community has mobilized to develop technological and financial solutions, progress towards true, systemic climate resilience remains uneven and often superficial. A central barrier to effective action is the persistent disconnect between the large-scale, often abstract, solutions developed by international bodies, governments, and technology firms and the specific, complex, and culturally-rooted needs of the communities most affected by climate change. This gap has led to a cycle of well-intentioned but ill-fitting interventions that are met with resistance, low adoption, and ultimately, unsustainable outcomes.